The Influence of a KDT501, a Novel Isohumulone, on Adipocyte Function in Humans - Finlin, Brian S.; Zhu, Beibei; Kok, Bernard P.; Godio, Cristina; Westgate, Philip M.; Grayson, Neile; Sims, Robert; Bland, Jeffrey S.; Saez, Enrique; Kern, Philip A. (Frontiers in Endocrinology, 2017)
Objective: In a phase II clinical trial in nine obese, insulin-resistant humans, we observed that treatment with KDT501, a novel isohumulone drug, increased total and high molecular weight adiponectin in plasma. The objective was to determine whether KDT501 increased adiponectin secretion from subcutaneous white adipose tissue (SC WAT) and the underlying mechanism(s). Methods: Nine obese participants with either prediabetes or with normal glucose tolerance plus three features of metabolic syndrome were part of the study. SC WAT biopsies were performed before and after 28 days of KDT501 treatment in a clinical research setting. In addition, a cold stimulus was used to induce thermogenic gene expression. Adiponectin secretion was measured, and gene expression of 130 genes involved in adipose tissue function was determined. The effect of KDT501 on adipocyte mitochondrial function was analyzed in vitro. Results: SC WAT explants secreted more total and HMW adiponectin after KDT501 treatment (P<0.05). After KDT501 treatment, a number of genes involved in thermogenesis and lipolysis were induced by cold (P<0.05). KDT501 also potentiated beta-adrenergic signaling (P<0.001) and enhanced mitochondrial function in adipocytes (P<0.001). Conclusions: KDT501 induced adiponectin secretion post-transcriptionally, and increased gene expression of thermogenic and lipolytic genes in response to cold stimulation. These beneficial effects on SC WAT may be explained by the ability of KDT501 to potentiate beta-adrenergic signaling and enhance mitochondrial function in adipocytes. ClinicalTrials.gov ID number: NCT02444910